Electric spark secondary deposition preparation method of CoCrFeNiAl high-entropy alloy composite coating containing diamond infiltrated layer

By preparing a CoCrFeNiAl high-entropy alloy composite coating containing diamond seepage layer on the surface of the steel component, the synergistic effect of high-entropy alloy, diamond and graphite is used to solve the friction and wear problem of steel components in a friction and wear environment, and achieve significant wear resistance and friction reduction performance improvement.

CN119553276APending Publication Date: 2025-03-04SHENYANG LIGONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411713696.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The friction and wear problems of the surface of steel components in friction and wear environments lead to shortening of equipment life and waste of resources.

Method used

The CoCrFeNiAl high-entropy alloy composite coating containing diamond seepage layer was prepared on the surface of the steel matrix by using electric spark secondary deposition technology. Through the synergistic action of high-entropy alloy, diamond and graphite, the wear resistance and friction reduction performance of the coating are improved.

Benefits of technology

It significantly improves the wear resistance and friction reduction performance of the surface of steel components, extends the service life of the equipment, and reduces production and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553276A_ABST
    Figure CN119553276A_ABST
Patent Text Reader

Abstract

The invention relates to the field of preparation of a wear-resistant composite coating on the surface of a steel member, in particular to an electric spark secondary deposition preparation method of a CoCrFeNiAl high-entropy alloy composite coating containing a diamond infiltrated layer, which is applied to coating the surface of a steel part. Steel is adopted as a base material, a CoCrFeNiAl high-entropy alloy electrode and a high-purity graphite electrode which are formed by sintering cobalt powder, chromium powder, iron powder, nickel powder and aluminum powder in an equal molar ratio are adopted as electrodes for electric spark deposition, and the CoCrFeNiAl high-entropy alloy composite coating containing the diamond infiltrated layer is deposited on the surface of the steel base by adopting an electric spark deposition technology. The composite coating and the steel substrate are metallurgically bonded with strong bonding force, the diamond infiltrated layer can enhance the surface hardness of the coating and reduce the friction coefficient of the surface of the composite coating, so that the composite coating has better antifriction and wear-resistant effects, and the problem of surface wear of a steel member in a frictional wear environment is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of wear-resistant composite coatings on the surfaces of steel components, and specifically to a method for preparing a CoCrFeNiAl high-entropy alloy composite coating comprising a diamond-infiltrated layer by electric spark secondary deposition, which can be applied to coating the surfaces of steel parts and has a significant friction-reducing and wear-resistant effect on the surfaces of the parts. Background Art

[0002] With the rapid development of science and technology, the fields of weapons and equipment, aerospace, transportation, etc., due to the continuous improvement of the requirements for a series of equipment parameters, the life of some important parts such as gun barrels, engine blades, armored vehicle bearings, etc. is getting shorter and shorter. The failure of these key components often occurs locally, and the entire replacement will cause a waste of resources and a long replacement cycle. In recent years, scientific researchers have continued to explore and believe that coating technology is currently a widely used and rapidly developing effective means to improve the service performance and life of components. Coating technology can enhance the surface performance of components, and even partially repair them after the failure of components. In this way, the service life of the components is increased, and time and cost are saved.

[0003] Among the numerous coating materials, high entropy alloys are emerging metal materials. Since Professor Ye Yunwei broke through the traditional alloy concept and proposed this emerging alloy concept in 2004, it has attracted widespread attention from all walks of life with its excellent performance. High entropy alloys have high entropy effects in thermodynamics, slow diffusion effects in kinetics, lattice distortion effects in structure, and "cocktail" effects. The high entropy effect can inhibit the formation of intermetallic compounds and promote the formation of a single solid solution structure; the lattice distortion effect makes the solid solution strengthening effect obvious, so that the performance of high entropy alloys will be improved accordingly; the "cocktail" effect is a composite effect of the interaction of the basic properties of each main element in the alloy, and the selection of different elements will affect the performance of the alloy. Under a series of strengthening effects, high entropy alloys have many excellent properties, such as high hardness, excellent wear resistance, high temperature oxidation resistance, etc. In current research, there are many studies on CoCrFeNi-based high entropy alloy coatings, especially CoCrFeNiAl coatings. CoCrFeNiAl high entropy alloys have good mechanical properties.

[0004] Electrospark deposition technology can be used to prepare coatings with excellent metallurgical bonding properties on the surface of metal substrates. It has the following advantages: (1) simple equipment and low cost; (2) the deposited layer is metallurgically bonded to the substrate and will not peel off; (3) it has little effect on the core temperature of the workpiece, no changes in organization and performance, and the workpiece will not anneal or deform; (4) it consumes less energy and material, and the electrode material can be widely selected according to the application; (5) it can be used to repair worn parts, with no size restrictions on the workpiece, and is especially suitable for local treatment of extra-large workpieces; (6) it is easy and safe to operate, and does not require high technical skills from the operator; (7) it does not pollute the environment and has low noise; (8) the thickness of the strengthening layer and the surface roughness can be adjusted by adjusting the electrical parameters and controlling the strengthening time to obtain different process effects; (9) the cost of strengthening and repairing parts is much lower than the cost of replacing parts. It can be widely used in the fields of weapons and equipment, aerospace, electronic communications and marine ships, especially in emergency repair and treatment, which is both convenient and efficient. Recent studies have shown that AlCoCrFiNi high-entropy alloy coatings, TiN coatings, Zr-based amorphous-nanocrystalline coatings, Ni-WS2, Mo-Si-B coatings, Cr-Al-Si-B coatings, and Ni-MoS2 coatings prepared by electrospark deposition technology can significantly improve the friction, wear, and high temperature resistance properties of the base material. Summary of the invention

[0005] The present invention aims to provide a method for preparing a CoCrFeNiAl high entropy alloy composite coating comprising a diamond-carburized layer by electrospark secondary deposition. The obtained high entropy alloy composite coating can solve the friction and wear problems on the surface of a steel substrate material under a friction and wear environment, ensure the safe and effective operation of steel components, and reduce production and maintenance costs.

[0006] The technical solution of the present invention is:

[0007] The invention discloses an electrospark secondary deposition preparation method for a CoCrFeNiAl high entropy alloy composite coating including a diamond-infiltrated layer. The substrate material is steel, and the electrodes used for electrospark deposition are CoCrFeNiAl high entropy alloy electrodes and high-purity graphite electrodes. The electrospark deposition technology is used to deposit the CoCrFeNiAl high entropy alloy composite coating including a diamond-infiltrated layer on the surface of the steel substrate.

[0008] The electric spark secondary deposition preparation method of the CoCrFeNiAl high entropy alloy composite coating containing a diamond-infiltrated layer adopts cobalt powder, chromium powder, iron powder, nickel powder and aluminum powder with an equal molar ratio and an average particle size of 300-500nm, and then sinters them into CoCrFeNiAl high entropy alloy electrodes by using spark plasma sintering technology after compression molding. The sintering temperature is 1050-1100°C, the sintering time is 10-20min, and the sintering pressure is 4-6 tons.

[0009] In the electric spark secondary deposition preparation method of the CoCrFeNiAl high entropy alloy composite coating containing a diamond infiltrated layer, nanometer-level graphite and diamond are dispersed in the CoCrFeNiAl high entropy alloy composite coating, and the mass percentage of graphite and diamond is 18% to 25%.

[0010] The electrospark secondary deposition preparation method of the CoCrFeNiAl high entropy alloy composite coating containing a diamond-infiltrated layer comprises the following specific steps:

[0011] (1) The cut substrate material is polished step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the substrate surface; a diamond grinding paste with a particle size of 2.5 μm is used for polishing; after polishing, the substrate material is placed in an alcohol container and cleaned with ultrasound for 300 to 600 seconds, and after cleaning, it is blown dry with a blower for standby use;

[0012] (2) Processing the CoCrFeNiAl high entropy alloy electrode into a shape suitable for electrospark deposition clamping, grinding it step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the electrode surface; polishing it with a diamond paste with a particle size of 2.5 μm; after polishing, placing the CoCrFeNiAl high entropy alloy electrode in an alcohol container, and cleaning it with ultrasound for 300 to 600 seconds, and after cleaning, drying it with a hair dryer for standby use;

[0013] (3) processing the high-purity graphite electrode into a shape suitable for electrospark deposition clamping for standby use;

[0014] (4) Electrospark deposition was performed under argon protection. The specific process parameters were: output power of 1200W to 1600W, output voltage of 60V to 80V, electrode speed of 1800 to 2200 rpm, and deposition rate of 2 to 4 min / cm 2 First, a CoCrFeNiAl high entropy alloy coating is deposited, and then a high-purity graphite electrode is used to perform a melt infiltration treatment on the deposited CoCrFeNiAl high entropy alloy coating.

[0015] In the electric spark secondary deposition preparation method of the CoCrFeNiAl high entropy alloy composite coating including a diamond-infiltrated layer, the argon gas flow rate is 8 to 12 L / min.

[0016] The electrospark secondary deposition preparation method of the CoCrFeNiAl high entropy alloy composite coating containing a diamond-infiltrated layer adjusts the content of graphite and diamond in the CoCrFeNiAl high entropy alloy composite coating by changing process parameters, argon gas flow rate and deposition rate.

[0017] The electric spark secondary deposition preparation method of the CoCrFeNiAl high entropy alloy composite coating containing a diamond infiltrated layer, in the graphite and diamond of the CoCrFeNiAl high entropy alloy composite coating, the mass percentage of graphite is 39.71-44.46%, and the mass percentage of diamond is 55.54-60.29%.

[0018] The electric spark secondary deposition preparation method of the CoCrFeNiAl high entropy alloy composite coating containing a diamond-infiltrated layer, the thickness of the CoCrFeNiAl high entropy alloy composite coating is 19.32μm to 65.37μm.

[0019] The design concept of the present invention is:

[0020] The core idea of ​​the present invention is to utilize the advantages of the electric spark technology to convert part of the graphite into diamond in the deposition process and infiltrate the coating. With the help of the high entropy effect and the synergistic effect of the diamond dispersion strengthening phase and the self-lubricating graphite, a coating with excellent friction reduction and wear resistance is obtained. Specifically as follows: Diamond has good dispersion strengthening and graphite self-lubricating effects. The present invention utilizes the advantages of the electric spark deposition technology, that is, it can produce ultrafine crystals or even nano-scale crystal structures during the deposition process to enhance the mechanical properties of the coating, and maximize the synergistic effect of high entropy alloys, diamonds, and graphite. At the same time, the substrate and the coating have a strong bonding force, the deposition equipment is low in price, easy to operate, and convenient for industrial application. In addition, the significant advantage of the present invention is that by controlling the flow rate of argon gas during the electric spark deposition process, the oxygen in the air in the electric spark deposition process is reduced to participate in the reaction. During the electric spark carburizing process, due to the instantaneous high temperature of the electric spark deposition process, a local high pressure is generated, causing the local graphite phase to change to a diamond phase, greatly improving the hardness of the coating and enhancing the wear resistance of the coating.

[0021] The advantages and beneficial effects of the present invention are as follows:

[0022] 1. The coating developed by the present invention has a strong metallurgical bond with the steel substrate, is not easy to peel off, and does not affect the mechanical properties of the substrate;

[0023] 2. The coating developed by the present invention contains an in-situ formed diamond phase, which can further improve the mechanical properties of the coating and make the coating have high hardness. The nanohardness of the high entropy alloy coating is 19.22GPa, and the Young's modulus is 286.2GPa; the nanohardness of the coating after carburization is 62.83GPa, and the Young's modulus is 669.1GPa. The nanohardness of the coating is 2.27 times higher than that of the substrate, and the elastic modulus of the coating is 1.34 times higher than that of the substrate. The H / E value of the coating is 0.4 times higher than that of the substrate, and the H / E value of the coating is 1.3 times higher than that of the substrate. 3 / E 2 The value increased by 5.39 times compared with the base.

[0024] 3. The coating developed by the present invention has excellent friction reduction and wear resistance effects;

[0025] 4. The coating developed by the present invention has a simple preparation process and is easy to realize industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The surface morphologies of CoCrFeNiAl coating and CoCrFeNiAl carburized coating. (b) is the enlarged view of area E in (a), (d) is the enlarged view of area F in (c), Cracks is crack, and Splashingfeature is splashing trace.

[0027] Figure 2 The cross-sectional morphology (a), (c) and line scan (b), (d) of CoCrFeNiAl coating and CoCrFeNiAl carburized coating. In Figures (b) and (d), the horizontal axis Distance represents the distance (μm), the vertical axis CPS represents the count rate, Coating is the coating, and Substrate is the substrate.

[0028] Figure 3 The X-ray diffraction (XRD) patterns of the CoCrFeNiAl coating and the CoCrFeNiAl carburized coating are shown in Figure 1. In the figure, the horizontal axis 2θ represents the diffraction angle (degree), and the vertical axis Intensity represents the relative intensity (au).

[0029] Figure 4 The friction coefficient and wear loss of PCrNi3MoV (A) steel, CoCrFeNiAl coating and CoCrFeNiAl carburized coating under a load of 9 N. In the figure (a), the horizontal axis Time represents time (min), and the vertical axis friction coefficient represents the friction coefficient. In the figure (b), the horizontal axis Materals represents the sample, and the vertical axis Abraison loss represents the wear loss (mg).

[0030] Figure 5 The surface morphology of wear scars on PCrNi3MoV(A) gun steel, CoCrFeNiAl coating and CoCrFeNiAl before carburizing coating under 9N normal force under scanning electron microscope (SEM). DETAILED DESCRIPTION

[0031] In the specific implementation process, the present invention adopts CoCrFeNiAl high entropy alloy electrode and graphite electrode, adopts electrospark deposition technology, and controls voltage, power and protective gas flow to prepare CoCrFeNiAl high entropy alloy composite coating containing diamond on the surface of steel substrate.

[0032] Below, the present invention is further described in detail with reference to the accompanying drawings and embodiments:

[0033] Example 1

[0034] The base material is PCrNi3MoVA steel. Aluminum powder, cobalt powder, chromium powder, iron powder, and nickel powder (particle size is 400nm) are pressed together and then sintered into CoCrFeNiAl high entropy alloy electrode by discharge plasma. The atomic ratio of cobalt powder, chromium powder, iron powder, nickel powder, and aluminum powder in the CoCrFeNiAl high entropy alloy electrode is an equimolar ratio. The sintering temperature is 1080°C, the sintering time is 10min, and the sintering pressure is 5 tons.

[0035] In this embodiment, the steps for preparing the CoCrFeNiAl high entropy alloy composite coating are as follows:

[0036] (1) The cut substrate material is polished step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the substrate surface; a diamond grinding paste with a particle size of 2.5 μm is used for polishing; after polishing, the substrate material and the sample are placed in an alcohol container and cleaned with ultrasound for 300 seconds. After cleaning, the substrate material and the sample are blown dry with a hair dryer for standby use.

[0037] (2) The CoCrFeNiAl high entropy alloy electrode was processed into a shape suitable for electrospark deposition clamping, and was polished step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the electrode surface; a diamond grinding paste with a particle size of 2.5 μm was used for polishing; after polishing, the CoCrFeNiAl high entropy alloy electrode was placed in an alcohol container and cleaned with ultrasound for 300 seconds. After cleaning, it was blown dry with a hair dryer for standby use.

[0038] (3) processing a graphite material electrode (purity ≥ 99.9999wt%) into a shape suitable for electrospark deposition clamping and setting aside;

[0039] (4) Electrospark deposition was performed under argon protection. The specific process parameters were: output power of 1600 W, output voltage of 80 V, electrode speed of 2000 rpm, argon flow rate of 12 L / min, and deposition rate of 2 min / cm 2 Firstly, a CoCrFeNiAl high entropy alloy electrode is used to deposit a CoCrFeNiAl high entropy alloy coating, and then a graphite material electrode is used to perform a melt infiltration treatment on the deposited CoCrFeNiAl high entropy alloy coating.

[0040] An HSR-2M reciprocating friction and wear testing machine was used, in which the friction and wear conditions were a reciprocating distance of 10 mm, a reciprocating speed of 500 r / min, a load of 9 N, a friction time of 10 min, and a GCr15 steel ball of Φ4 mm as the wear object.

[0041] In this embodiment, the atomic percentage of each element in the CoCrFeNiAl high entropy alloy coating is Co:Cr:Fe:Ni:Al=15.28:16.09:34.64:16.03:17.96, and the atomic percentage of each element in the CoCrFeNiAl high entropy alloy composite coating after carburizing is C:Co:Cr:Fe:Ni:Al=41.27:11.98:10.72:12.25:12.32:11.46, wherein: the content of graphite and diamond is approximately 41.27at% (19wt%), wherein the content of graphite is approximately 16.92at%, the content of diamond is approximately 24.35at%, the nanohardness of the coating is 19.22GPa, and the Young's modulus is 286.2GPa; the nanohardness of the coating after carburizing is 62.83GPa, and the Young's modulus is 669.1GPa. The nanohardness of the coating is 2.27 times higher than that of the substrate, and the elastic modulus of the coating is 1.34 times higher than that of the substrate. The H / E value of the coating is 0.4 times higher than that of the substrate, and the H 3 / E 2 The value increased by 5.39 times compared with the base.

[0042] like Figure 1 As shown in Figure 2, the surface morphology of CoCrFeNiAl and CoCrFeNiAl carburized coatings at different magnifications. Figure 1 In (a), there are traces of splashing on the coating surface (as shown by the arrow). This is because the electrode and the substrate form a short circuit, which instantly releases the capacitor energy. The current pulse generated by the short circuit generates a plasma arc with a temperature of 5000-25000K in a short time. The instantaneous high temperature induces the formation of metal droplets at the end of the electrode, which splash on the substrate surface at a high speed. However, after carburizing, the splashing appearance weakens and disappears, as shown in Figure 2. Figure 1 (c) In addition, Figure 1Microcracks can also be observed in (a) and (c) (as indicated by arrows), which should be caused by the thermal stress of electrospark deposition (ESD). Especially for materials with poor coating plasticity, the cracks are often more obvious. The cracks are significantly enlarged after carburizing the coating.

[0043] Figure 1 b is Figure 1 The enlarged appearance of area E in a. Figure 1 d is Figure 1 The enlarged appearance of area F in c is shown in Table 1. These areas were analyzed by X-ray energy dispersive spectroscopy (EDS).

[0044] Table 1 shows the EDS results of the surface of CoCrFeNiAl coating and CoCrFeNiAl carburized coating.

[0045] Location Al(at.%) Cr(at.%) Fe(at.%) Co(at.%) Ni(at.%) O(at.%) C (at.%) A 17.14 20.06 21.40 20.65 20.74 B 40.01 3.36 2.02 0.92 0.82 52.88 D 17.96 16.09 34.64 15.28 16.03 I 36.10 0.56 0.29 0.27 0.27 46.85 15.67 G 11.46 10.72 12.25 11.98 12.32 11.46 41.27 H 2.71 1.58 1.68 1.64 1.66 90.73

[0046] The content of each element in region A is close to 20% (At%) of the CoCrFeNiAl alloy electrode. This may be due to the "rapid quenching" effect during the electrospark deposition process. The molten metal droplets solidified before they could mix. Region B contains a large amount of Al and O elements, indicating that Al was oxidized during the coating deposition process. This region is Al oxide. Figure 1 a It can be seen that the coating surface presents a large number of irregularly shaped Al oxidation areas. Area D is the deposited CoCrFeNiAl high entropy alloy coating. The Al content is slightly reduced due to the oxidation reaction, and the Fe content is slightly increased. This is because the coating is prepared by coating on a steel substrate. During the heat release process of the electric spark, the elements between the coating and the substrate are diluted, resulting in the Fe content of the coating exceeding the original electrode content. After carburizing the coating, the C element is deposited in large quantities on the coating surface and is unevenly distributed. Area I contains a large amount of Al and O elements, indicating that area I is the same Al element oxidation deposition area as area B before carburizing. Area G is the appearance of the coating after carburizing. A large amount of C in area H has aggregated, and the C element content is relatively high.

[0047] like Figure 2 As shown in the figure, the cross-sectional morphology and EDS line scan results of the CoCrFeNiAl high entropy alloy coating before and after carburization. Figure 2 From a and c, it can be seen that the substrate and coating of CoCrFeNiAl and CoCrFeNiAl carburized coatings are tightly bonded without holes and cracks, and the maximum thickness of the coating is about 19.32μm to 64.36μm. Figure 2 From b and d, it can be seen that the content of element C is higher on the coating surface, while the content inside is relatively reduced.

[0048] like Figure 3As shown in the figure, the XRD patterns of CoCrFeNiAl coating and CoCrFeNiAl carburized coating (CoCrFeNiAl-C), CoCrFeNiAl coating is composed of face-centered cubic phase (FCC) and body-centered cubic phase (BCC), CoCrFeNiAl carburized coating is composed of FCC, BCC and graphite phase. Graphite does not form a compound in the coating, but is a single crystal independent phase, which is beneficial to the improvement of coating hardness. The BCC phase gradually weakens in the CoCrFeNiAl carburized coating, and the Graphite phase stands out.

[0049] As shown in Table 2, the nanohardness of the CoCrFeNiAl coating is 19.22 GPa and the elastic modulus is 286.2 GPa; the nanohardness of the coating after carburization is 62.83 GPa and the elastic modulus is 669.1 GPa. The nanohardness of the coating after carburization is 2.27 times higher than that before carburization, and the elastic modulus is 1.34 times higher. The H / E value is increased by 0.4 times, and H 3 / E 2 The value increased by 5.39 times. From the hardness and elastic modulus combined with the XRD results, it can be seen that during the carburizing process of the coating, due to the instantaneous high temperature, part of the graphite is transformed into diamond.

[0050] Table 2 shows the nanomechanical properties of CoCrFeNiAl coating and CoCrFeNiAl carburized coating

[0051] Sample E / Gpa H / GPa H / E <![CDATA[H 3 / AND 2 ]]> CoCrFeNiAl coating 286.2 19.22 0.067 0.0867 CoCrFeNiAl-C coating 669.1 62.83 0.094 0.5540

[0052] like Figure 4 As shown in Figure 2, the friction coefficient and wear volume of PCrNi3MoVA steel, CoCrFeNiAl coating and CoCrFeNiAl carburized coating. Figure 4 As shown in a, under the action of 9N load, the friction coefficients of PCrNi3MoVA steel, CoCrFeNiAl coating and carburized CoCrFeNiAl coating are 0.73, 0.48 and 0.25 respectively. Figure 4 As shown in b, the wear amount of the coating after carburizing is relatively the least, which shows that the coating after carburizing exhibits excellent wear resistance.

[0053] like Figure 5 As shown in the figure, under the action of 9N load, the wear surface morphology of the coating before and after carburization of PCrNi3MoVA steel and CoCrFeNiAl. Figure 5 It can be seen that clear friction-generated furrows appeared on the wear scar surfaces of PCrNi3MoVA steel and CoCrFeNiAl coating before and after carburization, accompanied by friction-generated debris. The surface debris of the coating after carburization is relatively more.

[0054] As shown in Table 3, the EDS results of the wear scar surface show that a certain degree of oxidation has occurred on the wear scar surface. J, O, and R are the surface appearances of the substrate and coating after friction, and slight oxidation has occurred.

[0055] Table 3 shows the EDS results of the wear scar surface of PCrNi3MoVA steel, CoCrFeNiAl coating and CoCrFeNiAl carburized coating under 9N normal force

[0056]

[0057]

[0058] The shear lip area L, black area K and debris M in the wear marks of PCrNi3MoVA steel contain a lot of O, indicating that severe oxidation has occurred. The shear lip area N and the friction and wear debris adhesion area P in the wear marks of CoCrFeNiAl coating are severely oxidized, and area Q contains a lot of Al and O, indicating that it is the surface Al oxide aggregation area. In the wear marks of CoCrFeNiAl coating after carburization, a large number of adhesion oxides produced by friction and wear are formed on the surface, such as areas S and T. The shear marks are not obvious. Area S contains a large amount of Al and O, indicating that it is the surface Al oxidation area formation. Area U contains a large amount of O and Fe, which may be the mixed debris of the friction pair and the coating during the friction process. The oxides produced during the friction process play an effective role in reducing wear. Therefore, it can be concluded that the wear type is oxidative wear accompanied by adhesive wear.

[0059] Example 2

[0060] The base material is 45 steel, and aluminum powder, cobalt powder, chromium powder, iron powder, and nickel powder (particle size is 500nm) are pressed together and then sintered into CoCrFeNiAl high entropy alloy electrode by discharge plasma. The atomic ratio of cobalt powder, chromium powder, iron powder, nickel powder, and aluminum powder in the CoCrFeNiAl high entropy alloy electrode is an equimolar ratio, the sintering temperature is 1060°C, the holding time is 15min, and the sintering pressure is 5 tons.

[0061] In this embodiment, the steps for preparing the CoCrFeNiAl high entropy alloy composite coating are as follows:

[0062] (1) The cut substrate material is polished step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the substrate surface; a diamond grinding paste with a particle size of 2.5 μm is used for polishing; after polishing, the substrate material and the sample are placed in an alcohol container and cleaned with ultrasound for 300 seconds. After cleaning, the substrate material and the sample are blown dry with a hair dryer for standby use.

[0063] (2) The CoCrFeNiAl high entropy alloy electrode was processed into a shape suitable for electrospark deposition clamping, and was polished step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the electrode surface; a diamond grinding paste with a particle size of 2.5 μm was used for polishing; after polishing, the CoCrFeNiAl high entropy alloy electrode was placed in an alcohol container and cleaned with ultrasound for 600 seconds. After cleaning, it was blown dry with a hair dryer for standby use.

[0064] (3) processing a graphite material electrode (purity ≥ 99.9999wt%) into a shape suitable for electrospark deposition clamping and setting aside;

[0065] (4) Electrospark deposition was performed under argon protection. The specific process parameters were: output power of 1600 W, output voltage of 80 V, electrode speed of 2000 rpm, argon flow rate of 8 L / min, and deposition rate of 3 min / cm 2 Firstly, a CoCrFeNiAl high entropy alloy electrode is used to deposit a CoCrFeNiAl high entropy alloy coating, and then a graphite material electrode is used to perform a melt infiltration treatment on the deposited CoCrFeNiAl high entropy alloy coating.

[0066] An HSR-2M reciprocating friction and wear testing machine was used, in which the friction and wear conditions were a reciprocating distance of 10 mm, a reciprocating speed of 500 r / min, a load of 9 N, a friction time of 10 min, and a GCr15 steel ball of Φ4 mm as the wear object.

[0067] In this embodiment, the atomic percentage of each element in the CoCrFeNiAl high entropy alloy coating is Co:Cr:Fe:Ni:Al=17.35:15.47:32.63:17.43:17.12, and the atomic percentage of each element in the CoCrFeNiAl high entropy alloy composite coating after carburizing is C:Co:Cr:Fe:Ni:Al=58.34:8.06:8.04:8.37:8.82:8.37, wherein: the content of graphite and diamond is approximately 58.34at% (19wt%), the content of graphite is approximately 23.92at%, the content of diamond is approximately 34.42at%, the nanohardness of the coating is 17.38GPa, the nanohardness of the coating after carburizing is 58.92GPa, the friction coefficient of the high entropy alloy coating is 0.38, the friction coefficient of the coating after carburizing is 0.33, and the friction coefficient of the 45 steel substrate is 0.75.

[0068] Example 3

[0069] The base material is Q235 steel. Aluminum powder, cobalt powder, chromium powder, iron powder, and nickel powder (particle size is 500nm) are pressed together and then sintered into CoCrFeNiAl high entropy alloy electrode by discharge plasma. The atomic ratio of cobalt powder, chromium powder, iron powder, nickel powder, and aluminum powder in the CoCrFeNiAl high entropy alloy electrode is an equimolar ratio. The sintering temperature is 1100°C, the holding time is 15min, and the sintering pressure is 5 tons.

[0070] In this embodiment, the steps for preparing the CoCrFeNiAl high entropy alloy composite coating are as follows:

[0071] (1) The cut substrate material is polished step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the substrate surface; a diamond grinding paste with a particle size of 2.5 μm is used for polishing; after polishing, the substrate material and the sample are placed in an alcohol container and cleaned with ultrasound for 480 seconds. After cleaning, the substrate material and the sample are blown dry with a hair dryer for standby use.

[0072] (2) The CoCrFeNiAl high entropy alloy electrode was processed into a shape suitable for electrospark deposition clamping, and was polished step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the electrode surface; a diamond grinding paste with a particle size of 2.5 μm was used for polishing; after polishing, the CoCrFeNiAl high entropy alloy electrode was placed in an alcohol container and cleaned with ultrasound for 480 seconds. After cleaning, it was blown dry with a hair dryer for standby use.

[0073] (3) processing a graphite material electrode (purity ≥ 99.9999wt%) into a shape suitable for electrospark deposition clamping and setting aside;

[0074] (4) Electrospark deposition was performed under argon protection. The specific process parameters were: output power of 1200 W, output voltage of 80 V, electrode speed of 2000 rpm, argon flow rate of 10 L / min, and deposition rate of 4 min / cm 2 Firstly, a CoCrFeNiAl high entropy alloy electrode is used to deposit a CoCrFeNiAl high entropy alloy coating, and then a graphite material electrode is used to perform a melt infiltration treatment on the deposited CoCrFeNiAl high entropy alloy coating.

[0075] An HSR-2M reciprocating friction and wear testing machine was used, in which the friction and wear conditions were a reciprocating distance of 10 mm, a reciprocating speed of 500 r / min, a load of 9 N, a friction time of 9 min, and a GCr15 steel ball of Φ4 mm as the wear object.

[0076] In this embodiment, the atomic percentage of each element in the CoCrFeNiAl high entropy alloy coating is Co:Cr:Fe:Ni:Al=17.17:17.58:32.66:17.39:15.2, and the atomic percentage of each element in the CoCrFeNiAl high entropy alloy composite coating after carburizing is C:Co:Cr:Fe:Ni:Al=48.23:10.79:10.48:11.51:10.01:8.98, wherein: the graphite and diamond contents are approximately 48.23at% (20wt%), the graphite content is approximately 19.77at%, the diamond content is approximately 28.46at%, the nanohardness of the coating is 15.34GPa, the nanohardness of the coating after carburizing is 56.96GPa, the friction coefficient of the high entropy alloy coating is 0.49, the friction coefficient of the coating after carburizing is 0.41, and the friction coefficient of the Q235 steel substrate is 0.78.

[0077] Example 4

[0078] The base material is 40Cr steel. Aluminum powder, cobalt powder, chromium powder, iron powder, and nickel powder (particle size is 300nm) are pressed together and then sintered into CoCrFeNiAl high entropy alloy electrode by discharge plasma. The atomic ratio of cobalt powder, chromium powder, iron powder, nickel powder, and aluminum powder in the CoCrFeNiAl high entropy alloy electrode is an equimolar ratio. The sintering temperature is 1050°C, the holding time is 20min, and the sintering pressure is 5 tons.

[0079] In this embodiment, the steps for preparing the CoCrFeNiAl high entropy alloy composite coating are as follows:

[0080] (1) The cut substrate material is polished step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the substrate surface; a diamond grinding paste with a particle size of 2.5 μm is used for polishing; after polishing, the substrate material and the sample are placed in an alcohol container and cleaned with ultrasound for 600 seconds. After cleaning, the substrate material and the sample are blown dry with a hair dryer for standby use.

[0081] (2) The CoCrFeNiAl high entropy alloy electrode was processed into a shape suitable for electrospark deposition clamping, and was polished step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the electrode surface; a diamond grinding paste with a particle size of 2.5 μm was used for polishing; after polishing, the CoCrFeNiAl high entropy alloy electrode was placed in an alcohol container and cleaned with ultrasound for 600 seconds. After cleaning, it was blown dry with a hair dryer for standby use.

[0082] (3) processing a graphite material electrode (purity ≥ 99.9999wt%) into a shape suitable for electrospark deposition clamping and setting aside;

[0083] (4) Electrospark deposition was performed under argon protection. The specific process parameters were: output power of 1200 W, output voltage of 60 V, electrode speed of 2000 rpm, argon flow rate of 9 L / min, and deposition rate of 4 min / cm 2 Firstly, a CoCrFeNiAl high entropy alloy electrode is used to deposit a CoCrFeNiAl high entropy alloy coating, and then a graphite material electrode is used to perform a melt infiltration treatment on the deposited CoCrFeNiAl high entropy alloy coating.

[0084] An HSR-2M reciprocating friction and wear testing machine was used, in which the friction and wear conditions were a reciprocating distance of 10 mm, a reciprocating speed of 500 r / min, a load of 9 N, a friction time of 10 min, and a GCr15 steel ball of Φ4 mm as the wear object.

[0085] In this embodiment, the atomic percentage of each element in the CoCrFeNiAl high entropy alloy coating is Co:Cr:Fe:Ni:Al=17.65:17.01:32.25:17.98:15.11, and the atomic percentage of each element in the CoCrFeNiAl high entropy alloy composite coating after carburizing is C:Co:Cr:Fe:Ni:Al=33.59:13.38:11.95:16.07:14.10:10.91, wherein: the content of graphite and diamond is approximately 33.59at% (25wt%), the graphite content is approximately 13.77at%, the diamond content is approximately 19.82at%, the nanohardness of the coating is 16.58GPa, the nanohardness of the coating after carburizing is 59.47GPa, the friction coefficient of the high entropy alloy coating is 0.49, the friction coefficient of the coating after carburizing is 0.41, and the friction coefficient of the 40Cr steel substrate is 0.81.

[0086] Example 5

[0087] The base material is H13 steel. Aluminum powder, cobalt powder, chromium powder, iron powder, and nickel powder (particle size is 500 nm) are pressed together and then sintered into CoCrFeNiAl high entropy alloy electrode by discharge plasma. The atomic ratio of cobalt powder, chromium powder, iron powder, nickel powder, and aluminum powder in the CoCrFeNiAl high entropy alloy electrode is an equimolar ratio. The sintering temperature is 1080°C, the holding time is 15 minutes, and the sintering pressure is 5 tons.

[0088] In this embodiment, the steps for preparing the CoCrFeNiAl high entropy alloy composite coating are as follows:

[0089] (1) The cut substrate material is polished step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the substrate surface; a diamond grinding paste with a particle size of 2.5 μm is used for polishing; after polishing, the substrate material and the sample are placed in an alcohol container and cleaned with ultrasound for 300 seconds. After cleaning, the substrate material and the sample are blown dry with a hair dryer for standby use.

[0090] (2) The CoCrFeNiAl high entropy alloy electrode was processed into a shape suitable for electrospark deposition clamping, and was polished step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the electrode surface; a diamond grinding paste with a particle size of 2.5 μm was used for polishing; after polishing, the CoCrFeNiAl high entropy alloy electrode was placed in an alcohol container and cleaned with ultrasound for 300 seconds. After cleaning, it was blown dry with a hair dryer for standby use.

[0091] (3) processing a graphite material electrode (purity ≥ 99.9999wt%) into a shape suitable for electrospark deposition clamping and setting aside;

[0092] (4) Electrospark deposition was performed under argon protection. The specific process parameters were: output power of 1200 W, output voltage of 60 V, electrode speed of 2000 rpm, argon flow rate of 11 L / min, and deposition rate of 4 min / cm 2 Firstly, a CoCrFeNiAl high entropy alloy electrode is used to deposit a CoCrFeNiAl high entropy alloy coating, and then a graphite material electrode is used to perform a melt infiltration treatment on the deposited CoCrFeNiAl high entropy alloy coating.

[0093] An HSR-2M reciprocating friction and wear testing machine was used, in which the friction and wear conditions were a reciprocating distance of 10 mm, a reciprocating speed of 500 r / min, a load of 9 N, a friction time of 10 min, and a GCr15 steel ball of Φ4 mm as the wear object.

[0094] In this embodiment, the atomic percentage of each element in the CoCrFeNiAl high entropy alloy coating is Co:Cr:Fe:Ni:Al=16.61:16.44:32.55:17.98:16.42, and the atomic percentage of each element in the CoCrFeNiAl high entropy alloy composite coating after carburizing is C:Co:Cr:Fe:Ni:Al=43.56:10.32:10.42:15.07:11.10:9.53, wherein: the content of graphite and diamond is approximately 43.56at% (20wt%), the graphite content is approximately 17.86at%, the diamond content is approximately 25.70at%, the nanohardness of the coating is 14.78GPa, the nanohardness of the coating after carburizing is 52.49GPa, the friction coefficient of the high entropy alloy coating is 0.41, the friction coefficient of the coating after carburizing is 0.29, and the friction coefficient of the H13 steel substrate is 0.71.

[0095] The results of the embodiment show that the CoCrFeNiAl high entropy alloy coating of the present invention is metallurgically bonded with a steel substrate (such as: gun steel PCrNi3MoVA, etc.) with strong bonding force, and the nano-scale diamond-infiltrated layer can enhance the surface hardness of the coating. The coating obtained by this process has excellent wear resistance, reduces the friction coefficient of the coating surface, and makes the coating have better friction reduction and wear resistance, among which:. Therefore, it is conducive to solving the wear problem of the surface of steel components under friction and wear environment, is easy to control, and is suitable for industrial application.

[0096] The above is only a preferred feasible embodiment of the present invention, and it cannot be used to limit the scope of the rights of the present invention. The coating is applied to the surface of the steel component, which can significantly improve the wear resistance of the steel component and can be used in the fields of military industry, aerospace, etc. Therefore, according to the technical scheme and technical ideas of the present invention, various other corresponding changes and deformations are still within the scope of protection covered by the present invention.

Claims

1. A method for preparing a CoCrFeNiAl high entropy alloy composite coating comprising a diamond-carved layer by secondary electrospark deposition, characterized in that: The substrate material is steel, the electrodes used for electrospark deposition are CoCrFeNiAl high entropy alloy electrodes and high-purity graphite electrodes, and the CoCrFeNiAl high entropy alloy composite coating including a diamond-infiltrated layer is deposited on the surface of the steel substrate using electrospark deposition technology.

2. The method for preparing a CoCrFeNiAl high entropy alloy composite coating comprising a diamond-carved layer by secondary electrospark deposition according to claim 1, characterized in that: Cobalt powder, chromium powder, iron powder, nickel powder and aluminum powder with an equal molar ratio and an average particle size of 300-500nm are used, and after compression molding, they are sintered using spark plasma sintering technology to form CoCrFeNiAl high entropy alloy electrodes. The sintering temperature is 1050-1100°C, the sintering time is 10-20min, and the sintering pressure is 4-6 tons.

3. The method for preparing the CoCrFeNiAl high entropy alloy composite coating comprising a diamond-carved layer by electrospark secondary deposition according to claim 1, characterized in that: Nano-scale graphite and diamond are dispersed in the CoCrFeNiAl high entropy alloy composite coating, and the mass percentage of graphite and diamond is 18% to 25%.

4. The method for preparing a CoCrFeNiAl high entropy alloy composite coating comprising a diamond-carved layer by secondary electrospark deposition according to claim 1, 2 or 3, characterized in that: The specific steps are as follows: (1) The cut substrate material is polished step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the substrate surface; a diamond grinding paste with a particle size of 2.5 μm is used for polishing; after polishing, the substrate material is placed in an alcohol container and cleaned with ultrasound for 300 to 600 seconds, and after cleaning, it is blown dry with a blower for standby use; (2) Processing the CoCrFeNiAl high entropy alloy electrode into a shape suitable for electrospark deposition clamping, grinding it step by step with sandpaper of 240#, 400#, 600#, 800#, 1000#, and 1500# to remove the oxide film on the electrode surface; polishing it with a diamond paste with a particle size of 2.5 μm; after polishing, placing the CoCrFeNiAl high entropy alloy electrode in an alcohol container, and cleaning it with ultrasound for 300 to 600 seconds, and after cleaning, drying it with a hair dryer for standby use; (3) processing the high-purity graphite electrode into a shape suitable for electrospark deposition clamping for standby use; (4) Electrospark deposition was performed under argon protection. The specific process parameters were: output power of 1200W to 1600W, output voltage of 60V to 80V, electrode speed of 1800 to 2200 rpm, and deposition rate of 2 to 4 min / cm 2 First, a CoCrFeNiAl high entropy alloy coating is deposited, and then a high-purity graphite electrode is used to perform a melt infiltration treatment on the deposited CoCrFeNiAl high entropy alloy coating.

5. The method for preparing the CoCrFeNiAl high entropy alloy composite coating comprising a diamond-carved layer by secondary electrospark deposition according to claim 4, characterized in that: The argon flow rate is 8-12 L / min.

6. The method for preparing the CoCrFeNiAl high entropy alloy composite coating comprising a diamond-carved layer by secondary electrospark deposition according to claim 4, characterized in that: The contents of graphite and diamond in the CoCrFeNiAl high entropy alloy composite coating can be adjusted by changing the process parameters, argon gas flow rate and deposition rate.

7. The method for preparing a CoCrFeNiAl high entropy alloy composite coating comprising a diamond-carved layer by secondary electrospark deposition according to claim 6, characterized in that: In the graphite and diamond of the CoCrFeNiAl high entropy alloy composite coating, the mass percentage of graphite is 39.71-44.46%, and the mass percentage of diamond is 55.54-60.29%.

8. The method for preparing a CoCrFeNiAl high entropy alloy composite coating comprising a diamond-carved layer by secondary electrospark deposition according to claim 4, characterized in that: The thickness of the CoCrFeNiAl high entropy alloy composite coating is 19.32μm to 65.37μm.